EFFECTS OF POST HARVEST DRYING ON KERNEL QUALITY OF MAIZE - M. A. Maqbool; M. Aslam; A. Beshir; M. S. Khan; M. Ahsan (Journal of Animal and Plant Sciences, 2019)
To overcome the prevailing vitamin A deficiency, provitamin A biofortified maize hybrids were introduced by CIMMYT in Pakistan. Provitamin A carotenoids are sensitive to light and temperature therefore, careful handling is prerequisite. Conventionally direct sun drying of cobs is practiced in the region after harvesting but there was need to optimize the post-harvest drying conditions to retain the nutritional value in biofortified maize hybrids. Direct and indirect sun drying was practiced in current study to evaluate the nutritional losses caused by direct exposure to sun light. Current experiment was conducted under completely randomized design with two factor factorial treatment structure with two replications. Experimental treatments were direct and indirect post-harvest sun drying of cobs. Experimental results showed that starch contents were affected negatively in maize cobs by direct exposure to sun light for drying. Losses in starch contents resulted in proportional increase of protein and oil contents in maize hybrids. Ash contents were also increased in direct sun drying of maize cobs relative to indirect (shade) sun drying. Significant losses of total carotenoid and pro-vitamin A contents were observed under direct exposure to sun light. Carotenoid pigment losses were attributed to susceptibility to oxidative damage and light absorption capacity. Indirect or shade drying harbored the favorable results to retain the optimal kernel quality traits. Among all studied exotic hybrids, HP1097-15 and HP1097-16 were more stable because these were subjected to minimum losses in kernel quality traits under direct sun drying. HP1097-15 was also high yielding based on grain yield among the tested hybrids. It is recommended that indirect (under shade) post-harvest drying of cobs should be practiced to avoid the nutritional losses in pro-vitamin A biofortified maize hybrids.
Keywords: Pro-vitamin A Biofortified; Shade; sundry; moisture; carotenoids; proteins; starch; shelf-life